Abstracts of the Rehabilitation and Therapy Research Society 9th Annual Conference. (February 2014) - French, Helen; Foley, Geraldine; Timonen, Virpi; Hardiman, Orla; Doherty, Orlaith; O'Mahoney, Mary; McCullough, Amanda; Hughes, Carmel; Tunney, Michael; Elborn, Stuart; Quittner, Alexandra; Bradley, Judy; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: People with motor neurone disease (MND) receive care from a broad range of healthcare professionals between symptom onset and end-of-life care. However, little is known about how and why MND service users engage with healthcare providers. The objective of this grounded theory (GT) study was to uncover key psychosocial processes which explain how people with MND interact with service providers. Method: 34 people with MND were theoretically sampled from the Irish MND population based register. In-depth and semi-structured interviews were conducted with each participant in their home. All interviews were digitally-audio recorded and transcribed. Transcriptions were member-checked prior to conceptual analysis. Data were coded using open, axial, and selective coding procedures. As for GT method, coding and memoing guided sampling. University ethical approval and medical research ethical approval was obtained. Findings and Discussion: This study found that people with MND live through unremitting loss and exert control over healthcare services to adapt to loss. Participants engaged with allied healthcare professionals (AHPs) from diagnosis to end-of-life care as they adapted to loss. Service users trusted and felt reassured by AHPs when AHPs were sensitive to how participants were coming to terms with loss. All participants accessed AHP care through public sector healthcare services and a minority engaged with private sector AHP services. Private sector services failed to reassure service users. Both micro-contexts (i.e. relationships) and macro-contexts (i.e. systems) shaped how AHPs enabled MND service users to adapt to loss. Participants 'connected' with AHPs when AHPs responded to their feelings of loss. As participants encountered more loss, they felt their needs were best met by public sector services. Conclusion: MND service users in the Republic of Ireland rely on public sector AHPs to cope with mounting loss. AHPs need to render control to service users as they adapt to loss.